Moderators of the personality-performance relationship: An investigation of job meaning and autonomy. Issue 3 (3rd April 2017) - Muldoon, Jeffrey; Kisamore, Jennifer L.; Liguori, Eric W.; Jawahar, I.M.; Bendickson, Joshua
Abstract : Purpose: The purpose of this paper is to investigate whether job meaning and job autonomy moderate the relationship between emotional stability and organizational citizenship behavior. Design/methodology/approach: In total, 190 supervisor-subordinate dyads completed three surveys. Linear and curvilinear analyses were used to assess the data. Findings: Results indicate emotionally stable individuals are more likely to perform OCBOs in low autonomy and/or low job meaning situations than are employees low in emotional stability. Conversely, individuals who have high autonomy and/or high meaning jobs are likely to engage in OCBOs regardless of personality. Research limitations/implications: As a survey-based research study, causal conclusions cannot be drawn from this study. Results suggest future research on the personality-performance relationship needs to more closely consider context and the potential for curvilinear relationships. Practical implications: Managers should note that personality may significantly affect job performance and consider placing individuals in jobs that best align with their personality strengths. Originality/value: This study sheds light on factors which may have led to erroneous conclusions in the extant literature that the relationship between personality and performance is weak.